A hybrid method of determining deformations of engineering structures with a laser station and a 3D scanner = Hybrydowa metoda wyznaczania odkształceń konstrukcji inżynierskich z wykorzystaniem stacji laserowej oraz skanera 3D - Sztubecki, Jacek; Bujarkiewicz, Adam; Derejczyk, Karol; Przytuła, Michał (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article presents the technology and an analysis of results of engineering structure displacements and deformation measurements. Two measuring technologies using the TDRA65000 laser station from Leica and the FARO Focus M scanner were applied during the tests.
Keywords: engineering constructions; geodetic measurements; measurements of displacements; determination of deformations; laser scanning; konstrukcje inżynierskie; pomiary geodezyjne; pomiar przemieszczeń; wyznaczanie odkształceń; skaning laserowy